2023
DOI: 10.1039/d3dt00773a
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell Mo2C@NC/Mo2C hollow microspheres as highly efficient electrocatalysts for the hydrogen evolution reaction

Abstract: Developing low-cost and highly efficient electrocatalysts for the hydrogen evolution reaction (HER) has stimulated extensive interest. Molybdenum carbide materials have been proposed as promising alternatives to noble platinum-based catalysts due...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The guanine moieties then form a CN-polymer through intramolecular hydrogen bonding in the presence of Zn 2+ ions. 27 Meanwhile, thiourea releases S 2− ions which react with Zn 2+ ions to form ZnS NPs. These ZnS NPs intertwine with the CN-polymer, giving rise to a hydrangea-like precursor.…”
Section: Resultsmentioning
confidence: 99%
“…The guanine moieties then form a CN-polymer through intramolecular hydrogen bonding in the presence of Zn 2+ ions. 27 Meanwhile, thiourea releases S 2− ions which react with Zn 2+ ions to form ZnS NPs. These ZnS NPs intertwine with the CN-polymer, giving rise to a hydrangea-like precursor.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks of Mo 4+ species at 229.5 eV/233.4 eV and the Mo 6+ species at 233.0 eV/ 236.2 eV are ascribed to MoO 2 and MoO 3 due to the partial oxidation of the surface, which are commonly observed when molybdenum carbide and molybdenum nitride are exposed to air. One can see that Mo 2+ and Mo 3+ species with peaks at 228.7 eV/231.0 eV and 229.0 eV/232.2 eV correspond to Mo 2 C or Mo 2 N, 34 which has been confirmed to be active in the electrocatalytic HER. 29 The spectra of N 1s were divided into three peaks corresponding to the Mo-N species (397.5 eV), pyridine N (399.5 eV), and graphite N (401.6 eV).…”
Section: Formation Mechanism Of the Core-shell Structurementioning
confidence: 94%
“…86 The outcomes indicated that MoSe 2 -Mo 2 C/NC exhibited a higher HER activity than MoSe 2 /NC and Mo 2 C/NC in acidic media. Notably, this material requires only a voltage of - 87 The authors prepared a core-shell architecture of Mo 2 C@NC/Mo 2 C via hydrothermal technique, as shown in Fig. 10a.…”
Section: Enhancement Strategies In Mo X C For Hermentioning
confidence: 99%